The International Review of the Red Cross and the protection of civilians, c. 1919–1939. (April 2018) - Holmes, Ben
Abstract: This article will use past issues of the International Review of the Red Cross to examine how the International Red Cross and Red Crescent Movement (the Movement) has engaged with the issue of civilian protection over the course of its history. Although founded to organize humanitarian relief and legal protection for wounded and sick combatants, the International Committee of the Red Cross and the wider Movement have increasingly incorporated civilian war victims into their remit since their establishment. Yet, as this article will highlight, this process has not been straightforward. Focussing on the critical period between the two World Wars, the article will use the Review to illustrate why the Red Cross began engaging with the "civilianization" of conflicts in response to the threat of new technologies like gas and aerial bombardment. Using articles from the Review to highlight the key challenges faced by the Movement in protecting civilians over this period, it will also consider the gaps in the Red Cross's initial conceptions of who "the civilian" was, why belligerents attacked them, and what was the best means of protecting them.